RANTES, MCP-1 chemokines and factors describing rheumatoid arthritis - Pavkova Goldbergova, Monika; Lipkova, Jolana; Pavek, Nikolas; Gatterova, Jindra; Vasku, Anna; Soucek, Miroslav; Nemec, Petr (Molecular immunology, 2012)
The MCP-1/CCL2 as well as RANTES/CCL5 chemokines are potent chemoattractants involved in immunoregulatory and inflammatory processes of rheumatoid arthritis. Recent studies demonstrated elevated levels of MCP-1 and RANTES in plasma, synovial fluid, and the synovial tissue of patients with RA. To examine the relationship among MCP-1 and RANTES single nucleotide polymorphisms and circulating levels and rheumatoid arthritis (RA), a total of 156 RA patients and 125 controls were recruited into the study. An association of -855 C/G MCP-1 polymorphism to IgM RF within the RA patients was observed. The lowest circulating levels of RANTES were observed in the AA variant of RANTES -403 G/A polymorphism. Furthermore, an association of -403 AA variant to circulating levels of IL-15 and IL-10 was found. No associations of factors describing rheumatoid arthritis (RFs, ANA, anti-CCP-positive/negative, DAS 28 score and number of swollen joints) with MCP-1 levels, genotype distribution, allelic frequencies and/or frequencies of haplotypes composed of all three studied polymorphisms in promoter region of MCP-1, and RANTES polymorphism were observed. We conclude that the RANTES promoter polymorphism is associated to circulating levels of RANTES, IL15 and IL10. However, our findings suggest that polymorphisms in the MCP-1 and RANTES gene promoters do not contribute significantly to the interindividual RA susceptibility and/or severity in Caucasians.
Keywords: dospělí; Arthritis, Rheumatoid; Female; revmatoidní artritida; Adult; interleukin-10; mladý dospělý; ženské pohlaví; Chemokine CCL5; jednonukleotidový polymorfismus; imunoglobulin M; lidé; Polymorphism, Single Nucleotide; synoviální tekutina; chemokin CCL5; Aged, 80 and over; Synovial Membrane; synoviální membrána; Interleukin-10; chemokin CCL2; Male; Aged; Immunoglobulin M; Chemokine CCL2; Young Adult; interleukin-15; Synovial Fluid; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; promotorové oblasti (genetika); Promoter Regions, Genetic; Middle Aged; Interleukin-15; Humans